PENGALAMAN PERSALINAN IBU DI RUMAH SAKIT PUSRI PALEMBANG MOTHER'S LABOR EXPERIENCE IN PUSRI PALEMBANG HOSP - Sutrisari Sabrina Nainggolan (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Every day there are around eight hundred thirty thousand mothers in the world die fromdiseases/complications related to pregnancy and childbirth. The cause of maternal death can bedue to maternal factors or factors from the fetus. Labor is a very important event in a woman's life.The experience that they feel while undergoing labor is certainly different. When a woman has theexperience of the first child with normal labor, there will be happiness and also a feeling of fearrelated to the condition of the fetus. Unlike the case when the woman gives birth to her secondchild by cesarean, there will be a feeling of worry, anxiety and fear. This feeling arises because thewoman will experience a labor condition that is different from the previous labor. Qualitativestudy of phenomenology to explore the experience of labor. Six participants, namely multigravidamothers, had experiences of normal labor and sectio, were willing to be participants, were able toexpress their labor experiences, and were in place when the study was conducted. Data wascollected through in-depth interviews twice which were completed with field notes. Interviewswere recorded and then transcripts of interviews were made and analyzed using the Collaiziapproach. The results of the study revealed three themes, namely the response at delivery, copingmechanism at delivery, and support obtained when facing labor. For nursing services, there needsto be an explanation for patients and families related to labor. This is important to reduce clientand family anxiety. In addition, the results of this study can be used as information in improvinghealth services not only from the biological side but on the psychological aspect of the mother